PROSES FORMULASI KEBIJAKAN PEMBANGUNAN DENGAN MENGGUNAKAN ANALISIS FORCASTING INDEKS PEMBANGUNAN MANUSIA: (Studi pada Pemerintah Kabupaten Sumba Barat Daya) - Kornelis Bali Mema (Jurusan Administrasi Publik, Fakultas Ilmu Administrasi, Universitas Brawijaya, 2023)
This research aims to; (1) know and analyze community empowerment policies using HDI forecasting analysis, and (2) know forecasting analysis of development policy formulation processes in the Southwest Sumba district. The research method used is mixed. Based on the results of the forecasting analysis, the three-year lag AR (1) forecasting model is obtained as the right model to predict the HDI for the 2022-2026 period. This analysis shows that if the current community empowerment policy is still implemented, then the HDI in the next five years tends to fluctuate. The preparation of the program has not used forecasting analysis but is based on an analysis of strategic problems and issues, the vision, and mission of regional heads, and the direction of national and provincial development. Planning documents are generally the result of plagiarism from several activity programs of the previous period.